Comparison of the efficacy and safety of warfarin anticoagulation and left atrial appendage transcatheter occlusion in the treatment of non-valvular atrial fibrillation and investigation of ET-1, hs-CRP and PDGFs: Warfarin anticoagulation and PLAATO in NVAF - Zhang, Yujie; Yao, Yali; Tao, Ling; Du, Tao; Jia, Binbin; Zhou, Mi; Zhang, Zhen (Cellular and Molecular Biology, 2024)
This study compared the therapeutic effect and safety between warfarin anticoagulation and percutaneous left atrial appendage transcatheter occlusion (PLAATO) in non-valvular atrial fibrillation (NVAF). A total of 110 patients were selected and assigned to Control group (n=55) and Observation group (n=55). The control patients were used warfarin, while the observation patients were performed PLAATO. The coagulation function, stroke and bleeding scores were compared between the two groups at different times. Left ventricular function before therapy and 1 year after therapy and adverse events during follow-up were compared between the two groups. After one month of treatment, CHA2DS2-VASC, HAS-BLED score, serum ET-1 and hs-CRP levels were lower in the PLAATO patients than in warfarin patients, but serum PDGFs levels were higher than patients in the warfarin patients (P < 0.05). One month after treatment, the activated partial thromboplastin time (APTT), prothrombin time (PT), and thrombin time (TT) of the PLAATO patients was longer than that of the warfarin patients (P < 0.05), but the levels of fibrinogen (FIB) in the PLAATO patients were lower than that of the warfarin patients (P < 0.05). In addition, one year after therapy, the left atrial end-diastolic volume (LAEDV), left atrial end-systolic volume (LAESV) and left atrial inner diameter of the two groups were significantly reduced (P < 0.05). Left atrial appendage (LAA) occlusion can effectively improve the cardiac function and coagulation function of NVAF patients, with lower incidence of bleeding events, stroke events and higher safety.